SappurisaDhamma : The Concept of Human Development - ศรีคชา พระใบฎีกาสวรรค์ กิตฺติวณฺโณ; แสงนภาวรรณ บรรจง (Journal of Educational Review Faculty of Education in MCU, 2018)
The best way for human development is through education. Education is an important tool to help create prosperity and solve problems of the country. The problems caused by human must be resolved from human. The Buddha is the model in self-development and sets himself as a teacher of human beings and celestial beings. The development is to enhance efficiency, thinking, doing, knowledge, skills and desirable attitude through learning and training. The self- development used by the Buddha is through the codes called Dhamma-Vinaya. The codes are suitable for each group of trainees. 227 precepts are for monks, 331 precepts for nuns, 10 precepts for novices and the five precepts are the basis for lay-people.